RIGHT TO BE FORGOTTEN AS A FUNDAMENTAL HUMAN RIGHT - Yüce, Nisan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the main objective of this paper is to study the right to be forgotten as a fundamental human right and its legal basis. Methods of research: general scientific, philosophical and specially-legal methods of scientific research have been used. A system analysis method was used to determine the term of the right to be forgotten and regulations related to the right. The case method and doctrinal research method were used for determining the general understanding of the right. A dogmatic method was valuable to formulate conclusions and recommendations of practical character within the research issues concerning the correct and effective usage of the right. Results: the growing pace and place of the Internet have put the processing of personal data in a new light, and it is now accepted as a fundamental human right to request to be removed from any databases under the provisioned circumstances, thus, “to be forgotten.” To examine the right further, studies have been made both by international and national authorities. While the right to be forgotten must be exercised with the utmost care, it must be ensured that it does not conflict with the freedom of expression and freedom of the press; the balance between legal interest and rights must be maintained. Discussion: it was based on the scope and limitations of the right to be forgotten and the effectiveness of current laws.